The Roles of Education in Mitigating Child Abuse in Nigeria: The Strategies and Prospects - Udoakpan , Theresa Ndipmong; Piate, Rosemary Collins (Journal of Innovation in Education and Social Research, 2025)
The study examined the roles of education in mitigating child abuse in Nigeria, assessing the strategies and prospects. Descriptive survey design was adopted to carry out this research in Nigeria. The targeted population for the study comprised all social scientists in Nigeria. Stratified sampling technique was used to select 80 social scientists each from South South (Akwa Ibom State), South East (Abia) and South West (Lagos) which gave a sample size of 240 used to carry out this research. The instrument used for data collection was a structured questionnaire titled “Strategies and Prospects of Education in Child Abuse Questionnaire (SPECAQ)”. Face and content validation of the instrument was carried out by an expert in test, measurement, and evaluation in order to ensure that the instrument has the accuracy, appropriateness, and completeness for the study under consideration. The reliability coefficient obtained was 0.94, and this was high enough to justify the use of the instrument. The researcher subjected the data generated for this study to appropriate statistical technique such as descriptive statistics to answer research questions. The findings from the analysed data revealed that physical abuse was the most notorious form of child abuse prevalent in Nigeria. It also showed that the most effective role of education in mitigating child abuse was by raising awareness and prevention. The study concluded that education serves as a powerful tool in mitigating child abuse in Nigeria by raising awareness, fostering protective behaviors, and driving societal change. One of the recommendations made was that the Nigerian educational system should incorporate child abuse awareness programs into primary and secondary school curricula.